2021
DOI: 10.1007/s12144-021-01404-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived social support on fear of missing out (FoMO): A moderated mediation model

Abstract: Fear of Missing Out (FoMO) is a pervasive phenomenon among college students that may negatively affect the physical and mental health of individuals. Perceived social support, as one of the effective protective factors, can mitigate the harmful effects of FoMO, but few studies to date have examined the potential mechanisms underlying this relationship. The present study conducted an investigation involving 806 college students in China and used scales measuring perceived social support, basic psychological nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…In addition, negative feelings and distress also make individuals vulnerable to experiencing fear of missing out. This ICoPsy is in line with research conducted by [24] which explains that individuals with high fear of missing out scores feel their weak social support so that their basic psychological needs cannot be met, thus making them divert their feelings of isolation by pursuing information or moments. on social media.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, negative feelings and distress also make individuals vulnerable to experiencing fear of missing out. This ICoPsy is in line with research conducted by [24] which explains that individuals with high fear of missing out scores feel their weak social support so that their basic psychological needs cannot be met, thus making them divert their feelings of isolation by pursuing information or moments. on social media.…”
Section: Discussionsupporting
confidence: 86%
“…This causes more intensive usage of social networking sites (Gezgin et al, 2018). People with high levels of FoMO may pay more attention to the moods of other people that they have positive social interactions with (Dou et al, 2021) and may show a higher need for approval. This leads to more use of social media among these people (Alt & Boniel-Nissim, 2018).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…For example, Wang et al [ 7 ] used it to test the relation between the need to belong and authentic self-presentation on SNSs, and indicated that FoMO mediated the association between the need to belong and adolescent authentic self-presentation on SNSs. Dou et al [ 8 ] employed the FoMO moderated mediation model to explore the relationship between perceived social support and FoMO. They concluded that perceived social support was negatively associated with FoMO, and psychological needs partially mediated the relationship between perceived social support and FoMO.…”
Section: Fear Of Missing Out (Fomo) Moderated Mediation Modelmentioning
confidence: 99%